2012
DOI: 10.17221/91/2011-cjfs
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted phosphorylation of soybean protein isolates and their physicochemical properties

Abstract: Wang X.B., Chi Y.J. (2012): Microwave-assisted phosphorylation of soybean protein isolates and their physicochemical properties. Czech J. Food Sci., 30: 99-107.In order to improve the functional properties of soybean protein isolates (SPI), microwave-assisted phosphorylation (MAP) was applied. The result showed that after microwaving at 600 W for 3 min, the phosphorylation level of SPI reached 35.72 mg/g, emulsifying activity and stability were increased 2 times and 1.4 times, respectively, the solubility was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 22 publications
2
15
0
Order By: Relevance
“…So far, no one has phosphorylated PPI, so our results can only be compared with other protein phosphorylation results. Wang & Chi () had phosphorylated SPI. The results showed that the solubility of SPI after phosphorylation increased by 26%, which was lower than that of our results.…”
Section: Resultsmentioning
confidence: 99%
“…So far, no one has phosphorylated PPI, so our results can only be compared with other protein phosphorylation results. Wang & Chi () had phosphorylated SPI. The results showed that the solubility of SPI after phosphorylation increased by 26%, which was lower than that of our results.…”
Section: Resultsmentioning
confidence: 99%
“…The FTIR spectra were recorded with 64 scans at 4 cm À1 resolution from 4000 to 400 cm À1 at 25°C. The software ''Peakfit Version 4.12" was used to analyze the secondary structure of protein, and ''Gaussian peak fitting" was the algorithm used (Wang & Chi, 2012).…”
Section: Fourier Transform Infrared (Ftir) Spectroscopy Measurementmentioning
confidence: 99%
“…The surface sulfhydryl group and cysteine content of soymilk is shown in Table . Some processing methods such as heating, high pressure, oxidation and reduction may lead to chemical, conformational and changes in environment of sulfhydryl groups . Compared to full‐fat soymilk (20.75 µmol g −1 ), low‐fat soymilk had a similar content, 19.30 µmol g −1 , of surface SH group ( P > 0.05).…”
Section: Resultsmentioning
confidence: 99%
“…Some processing methods such as heating, high pressure, oxidation and reduction may lead to chemical, conformational and changes in environment of sulfhydryl groups. 24 Compared to full-fat soymilk (20.75 μmol g −1 ), low-fat soymilk had a similar content, 19.30 μmol g −1 , of surface SH group (P > 0.05). After the two-step heating method, the surface SH group content of low-fat soymilk increased to 26.64 μmol g −1 .…”
Section: Free Sulfhydryl Groups and Total Cysteine Content In Soymilkmentioning
confidence: 91%